2020
DOI: 10.1556/2006.2020.00043
|View full text |Cite
|
Sign up to set email alerts
|

The psychometric properties of the Revised Illness Perception Questionnaire (IPQ-R) regarding Internet gaming disorder in a general population of Chinese adults

Abstract: Background and aimsInternet gaming disorder (IGD) has been recognized as a mental illness. Cognitive and emotional illness representations affect coping and health outcomes. Very little is known about such perceptions related to IGD, in both general and diseased populations. This study examined the psychometric properties of the Revised Illness Perception Questionnaire (IPQ-R) for IGD in a general population that included mostly non-cases while a small proportion of the sample was IGD cases.MethodsAn anonymous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 56 publications
4
7
0
Order By: Relevance
“…Since such people may have suffered from the IGD symptoms for at least 1 year, they have a better understanding of the fact that IGD can affect their daily life significantly and be chronic and cyclical. This is also consistent with the finding in the cross-sectional study in Macao [ 33 ]. In addition, people with IGD may have already experienced failure in attempting to regulate their internet gaming behaviors and thus perceive a great sense of helplessness and hopelessness as well as a low sense of self-control, self-efficacy, and personal control for their internet gaming behaviors and IGD symptoms.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Since such people may have suffered from the IGD symptoms for at least 1 year, they have a better understanding of the fact that IGD can affect their daily life significantly and be chronic and cyclical. This is also consistent with the finding in the cross-sectional study in Macao [ 33 ]. In addition, people with IGD may have already experienced failure in attempting to regulate their internet gaming behaviors and thus perceive a great sense of helplessness and hopelessness as well as a low sense of self-control, self-efficacy, and personal control for their internet gaming behaviors and IGD symptoms.…”
Section: Discussionsupporting
confidence: 93%
“…Since the dimensions represent different perceptions of a disease and some perceptions may be particularly relevant to the disease, it is reasonable that not all the dimensions of illness representations of IGD were significantly correlated with IGD symptoms. Consistently, the recent cross-sectional study also reported that only timeline cyclical, personal control, illness coherence, and emotional representations were significantly correlated with IGD symptoms [33]. Similar results were also found in previous studies of other diseases (eg, [32,40]).…”
Section: Principal Findingssupporting
confidence: 89%
See 3 more Smart Citations